1989
DOI: 10.1088/0022-3727/22/11/023
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation history effect of a water-metal Berthelot tube system interpreted by an elaborated gas-trapping crevice model

Abstract: A stainless steel container, filled with 1 g of water and sealed with a copper plug, was repeatedly heated and cooled over an appropriate temperature range (temperature cycles). Negative pressures, although scattered, increased with temperature cycle repetition through two stages. The cavitation history effect persisted for continued temperature cycles after renewal of only the water. The authors found two efficient means of raising the negative pressure by the cavitation history effect: (i) a high repetition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 15 publications
0
13
0
2
Order By: Relevance
“…Ordinarily G(T,P) is determined for P > 0, then extended to the fluid under tension. In an actual Berthelot experiment the pressure which is developed can be measured by determining the deformation of the container 22 [which some, Henderson and Speedy for example, 20 construct in the form of a delicate spiral (an in situ Bourbon gauge)], or can be calculated from the temperature as outlined above. Alternatively, it may be possible to incorporate a strain guage or other type pressure guage into the sample cell, but this will be only at the risk of introducing new sites for heterogeneous nucleation.…”
Section: Methodsmentioning
confidence: 99%
“…Ordinarily G(T,P) is determined for P > 0, then extended to the fluid under tension. In an actual Berthelot experiment the pressure which is developed can be measured by determining the deformation of the container 22 [which some, Henderson and Speedy for example, 20 construct in the form of a delicate spiral (an in situ Bourbon gauge)], or can be calculated from the temperature as outlined above. Alternatively, it may be possible to incorporate a strain guage or other type pressure guage into the sample cell, but this will be only at the risk of introducing new sites for heterogeneous nucleation.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, sample liquids of Berthelot tube had undergone boiling and ultrasonic radiation to purge gases in the liquids for generation of negative pressures (Ohde, et al, 1989). In this study, it was found that the bacterial solution which had not experienced the treatments could generate the negative pressures higher than ca.…”
Section: Resultsmentioning
confidence: 86%
“…3b) can be measured directly from the wall-deformation, although this works only in thin-walled metal cells (when the sealing has been done by a soft-metal plug) [23] or in spiral-shaped glass cells (where the spiral can open and close as the pressure increase or decrease) [24]. An alternative way is the calculation of the pressure which requires the knowledge of the thermal expansions and compressibilities of the liquid and glass.…”
Section: Experimental Methods To Generate Negative Pressure In Liquidsmentioning
confidence: 99%